Adaptation and validation of the Chinese versions of the childhood perceived poverty and wealth questionnaire(C‑CPPWQ) and the childhood perceived unpredictability questionnaire (C‑CPUQ) - Yinqing Fan; Chenyu Yuan; Ge Song; Zhen Wang (BMC Psychology)
Abstract Background Childhood subjective socioeconomic status (operational definition of harshness) and unpredictability significantly influence life history strategies and subsequent psychological and behavioral patterns. Existing research on Chinese populations has been limited by inconsistent metrics and inadequate measurement items. This study aimed to adapt and validate the Chinese versions of the Childhood Perceived Poverty and Wealth Questionnaire (C-CPPWQ) and the Childhood Perceived Unpredictability Questionnaire (C-CPUQ), addressing cultural differences and expanding measurement subjects. Methods We conducted Exploratory Factor Analysis (EFA) with 493 students and Confirmatory Factor Analysis (CFA) with 1217 students to validate the factor structures. Concurrent validity was assessed using correlations with life history strategies (Mini-K) and childhood trauma (CTQ-SF) and reliability were also evaluated. Results The C-CPPWQ’s two-factor model (perceived wealth and perceived poverty) demonstrated good fit (CFI = 0.95; TLI = 0.94; SRMR = 0.05; RMSEA = 0.08) and strong internal consistency (alpha = 0.90), with significant correlations with Mini-K (r = -0.28, p < 0.001) and childhood trauma (r = 0.29, p < 0.001). The C-CPUQ’s three-factor model (Unpredictability of Parenting, Unpredictability of External Environment, and Unpredictability of Daily Happening) also showed a good fit (CFI = 0.96; TLI = 0.95; SRMR = 0.04; RMSEA = 0.07) and high reliability (alpha = 0.95), with significant correlations with Mini-K (r = -0.39, p < 0.001) and childhood trauma (r = 0.72, p < 0.001). Conclusions The newly adapted 14-item C-CPPWQ and 16-item C-CPUQ for Chinese contexts exhibit satisfactory psychometric properties, making them valuable tools for researching and evaluating childhood adversity.